The Intersection of SARS-CoV-2 and Diabetes - Jacob H. Nichols; Amber M. Smith; Colleen B. Jonsson (Microorganisms)
The interplay between comorbidities and viral infections is a critical factor that influences disease severity and outcomes. Diabetes Mellitus (DM) is one such comorbidity that significantly elevates the risk of severe viral infection from coronaviruses, namely, SARS-CoV-2. DM is characterized by either a lack of insulin production (type 1 diabetes) or insulin resistance (type 2 diabetes), both of which contribute to a state of hyperglycemia, or high blood sugar. Hyperglycemia significantly promotes chronic inflammation, metabolic dysfunction, and immune dysregulation, which put diabetics at an elevated risk of critical health outcomes. Additionally, diabetes is hypothesized to amplify viral titers during infection by promoting the expression of the viral entry receptor ACE2 and providing a favorable cellular energy environment for viral replication. This review focuses on explaining the mechanisms that link diabetics with more severe COVID-19 disease and exploring some of the mechanisms that contribute to the phenomenon where COVID-19 can promote new-onset diabetes. By highlighting the interconnections between diabetes and COVID-19, this review aims to emphasize the implications that the SARS-CoV-2 outbreak has had on metabolic health.